Upaya Pola Asuh Orang Tua Dalam Mengembangkan Kognitif dan Operasional Kongkret Anak Pertengahan (7-11) - Hafizah Wichayani Rawi; Adliya Salsabila; Nurhayati Harahap; Nur Ainun; Syahvira Rachman; Fauziah Nasution (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
The middle stage of the child starts from 7-11 years. At this stage the child is able to think which is good and bad, as well as socio-emotional. The importance of parenting style in educating children’s development. In the cognitive development of children, the parenting style of their parents play a very important role. Parenting consists of 3: (1) authoritarian, (2) authorative, (3) permissive. Of the several parenting styles that are suitable for good parenting, this is authorative parenting, where parents are warm and supportive of everything their children do. This research aims to provide more accurate information about parenting styles for children. It is hoped that this journal will add insight to readers in parenting. This research uses the literature study method, where we examine from one journal to another. Keywords: Middle ages, Parenting style, Concrete opaerations.